1989
DOI: 10.1113/expphysiol.1989.sp003253
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gastrin in the Development of the Gastrointestinal Tract in Fetal Sheep

Abstract: We have investigated the role of gastrin in the development of the gastrointestinal tract during the latter part of gestation in fetal sheep. We surgically removed the major source of gastrin, the gastric (abomasal) antrum, from five fetuses at 90 days of gestation. The remaining abomasum was anastomosed to the pylorus allowing unobstructed flow of luminal contents. Another five fetuses, subjected to sham-antrectomies at 90 days, served as controls. Further surgery was performed in all fetuses at 120 days for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In the developing rat (from fetal stage until weaning), the oxyntic mucosa would be under functional and trophic control of circulating gastrin and it was thought therefore that gastrin would play a role in the maturation and growth of the mucosa. This was particularly demonstrated after antrectomy in fetal sheep (Avila et al 1989) following parenteral nutrition or oral ingestion in the rat . But it was recently shown that gastrin affects neither the oxyntic mucosa nor the endocrine cells before weaning in rat stomach.…”
Section: Local Effects Of Cholecystokinin and Gastrin In The Gutmentioning
confidence: 99%
“…In the developing rat (from fetal stage until weaning), the oxyntic mucosa would be under functional and trophic control of circulating gastrin and it was thought therefore that gastrin would play a role in the maturation and growth of the mucosa. This was particularly demonstrated after antrectomy in fetal sheep (Avila et al 1989) following parenteral nutrition or oral ingestion in the rat . But it was recently shown that gastrin affects neither the oxyntic mucosa nor the endocrine cells before weaning in rat stomach.…”
Section: Local Effects Of Cholecystokinin and Gastrin In The Gutmentioning
confidence: 99%
“…There are however other important factors in GI development, notably the passage of fluid through the lumen (Trahair, Harding, Bocking, Silver & Robinson, 1986). The presence of gastrin, secreted by the fetal antrum, may have a trophic effect on the maturation of small intestinal villi (Avila, Harding, Young & Robinson, 1989). In addition to morphological changes, the induction of a number of GI enzymes occurs just before birth; these include increases in G-6Pase as well as rises in pancreatic and intestinal digestive enzymes (Calvert, 'Malka & Menaid, 1979;Henning, 1985) and it seems likely that corticosteroids play a part in these changes.…”
Section: Fetal Changesmentioning
confidence: 99%
“…Taken together, these diverse observations suggest that fetal endocrine cells release their secretory products in a regulated manner, and that peptides are capable to interfere with functional targets. The hypothesis is substantiated by the alteration of the development of intestinal mucosa when circulating concentrations of gastrin are decreased by antrectomy in sheep [4]. In this context, the significant positive correlation that was observed here between fetal plasma gastrin concentration and the growth of pancreas and stomach suggests that the relatively high circulating levels of this peptide may be relevant for trophicity.…”
Section: Discussionmentioning
confidence: 51%
“…Oldham and Thompson [3] have stressed the lack of knowledge on the effects of these peptides in the fetus. However, decreased plasma gastrin induced by antrectomy results in a lower development of gut mucosa in fetal lamb, and it was found that somatostatin infusion depressed plasma gastrin and pancreatic polypeptide (PP) [4]. During the last month of fetal life, the increasing plasma peptide concentration probably contributes to the growth of the digestive tract as well as to the enzyme content of the gastric and intestinal mucosa, and that of pancreas.…”
Section: Introductionmentioning
confidence: 99%